A Review of Innovations in Rhegmatogenous Retinal Detachment Surgical Techniques - Achia Nemet; Ala Moshiri; Glenn Yiu; Anat Loewenstein; Elad Moisseiev (Journal of Ophthalmology)
Rhegmatogenous retinal detachment (RRD) requires surgical intervention for its repair. There are variable techniques used for this purpose, and they are all being continuously refined. In this review, we detail the recent innovations in surgical management of RRD and proliferative vitreoretinopathy (PVR).